2021
DOI: 10.3390/medicines8110070
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Medical Imaging Case Volumes in Aseer Region: A Retrospective Study

Abstract: COVID-19 has had a significant impact on global health systems. The aim of this study was to evaluate how imaging volumes and imaging types in radiology departments have been affected by the COVID-19 pandemic across different locations. Methods: Imaging volumes in the Aseer region (in the south of Saudi Arabia) across main hospitals were reviewed retrospectively including all cases referred from different locations (outpatient, inpatient and emergency departments). Data for years 2019 and 2020 were compared. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…A subtotal of 41 [ 14 , 15 , 20 , 21 , 29 , 30 , [32] , [33] , [34] , 37 , 40 , 42 , 44 , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ] and 12 [ 20 , 21 , 42 , 65 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] ] studies reported diagnosis, and breast imaging outcomes, respectively. Key results from the individual studies are summarised narratively below, and presented in more detail in Table 2 and AppxTable F.6-F.8 ( Appendix F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subtotal of 41 [ 14 , 15 , 20 , 21 , 29 , 30 , [32] , [33] , [34] , 37 , 40 , 42 , 44 , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ] and 12 [ 20 , 21 , 42 , 65 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] ] studies reported diagnosis, and breast imaging outcomes, respectively. Key results from the individual studies are summarised narratively below, and presented in more detail in Table 2 and AppxTable F.6-F.8 ( Appendix F ).…”
Section: Resultsmentioning
confidence: 99%
“…In medical imaging studies or studies with a mixed screening and symptomatic population (AppxTable F.8a), the number of mammography examinations during the pandemic [ 20 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] ] generally showed a relative reduction of between 8.9% [ 84 ] and 92.7% [ 81 ], with 67% (6/9) of studies reporting cumulative (or average) reductions of 9%–37% [ 20 , [77] , [78] , [79] , 82 , 83 ]. In an additional 6 studies of symptomatic populations (AppxTable F.8b) [ 20 , 21 , 29 , 37 , 42 , 73 ], a similar reduction was found for the number of diagnostic mammography (range: 4.7%–83.8%) with half of the studies observing reductions between 4% and 21% [ 20 , 29 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there was the possibility that the patients who did not present for follow-up or who, based on the data from the university’s medical system, did not appear to have presented before a multidisciplinary team, may have received care at another institution. In addition, the COVID-19 pandemic also introduced changes in patient pathways, as it did in other countries involved with this pandemic [ 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies addressing the impact of COVID-19 on imaging volume in Saudi Arabia are scarce. An observational study conducted by Alelyani et al 19 demonstrated a 21.27% reduction in the overall imaging conducted across chief hospitals in the Aseer region (located in the southern part of Saudi Arabia). Our study depicted the way our facility-based experience and data, which utilized management software for the standardization and optimization of CT protocols, helped to overcome the downward trend in the frequency of imaging reported by other hospitals during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%